A NON FINISHED PAST: REFLECTIONS ABOUT OWN DISAPPEARANCE EXPERIENCE AND ITS CURRENT PERSISTENCES - Lampasona, Julieta (Centro de Investigaciones y Estudios sobre Cultura y Sociedad, 2017)
Departing from the idea that lived experience inside the Clandestine Detention Centers (CDC) constitutes a “limit experience” which effects continue to emerge in the present, the aim of this article is to understand the modes of emergence and/or persistence of lived violence in the subjective space. Based on the analysis of in-depth interviews to survivors of the CDC in Argentina, I analyze the modalities of irruption / disruption produced in certain survivors' narratives to refer to the experience of their (own) disappearance. The persistence of these narratives forms refers, on the one hand, to a temporality of stalk and rupture. But, on the other hand, it also alludes to new temporalities that (far from subsume subject in the continuous, pervasive and paralyzing time of violence) turns life possible in terms of future projections and subject's affirmation in its present.